Analysis of Financial Speculators’ Herd Behaviour Impact on the Instability of Commodity Prices. Evidence from Weekly WTI Crude Oil Market Data Using Uncertainty Theory (2018–2024) - Djamal, Tebache; Saida, Chetbani (Analiza wpływu zachowań stadnych spekulantów finansowych na niestabilność cen surowców. Dowody z tygodniowych danych z rynku ropy naftowej WTI z wykorzystaniem teorii niepewności (2018–2024), 2025)
Aim: The purpose of this paper is to model the herd behavior of financial speculators in order to demonstrate its effect on the instability of commodity prices, particularly WTI crude oil prices, following recent events: the COVID-19 pandemic, the war in Ukraine and the war in the Middle East. Methodology: The authors approach relies on introducing uncertainty theory and VNM1 expected utility, rather than relying on ARDL modelling and dummy variables over the period 2018–2024, using weakly data provided by the CFTC. Results: Our findings indicate the significant effect of variables, buying and selling positions of financial speculators and the war in Ukraine, namely increasing mimetic behavior of traders’ and financial speculators’ impact on prices. This result is valuable for a short-term relationship; however, there is no long-term relationship, which means no co-integration which can be interpreted by the efficiency of WTI crude oil market in long term. Implications and recommendations: The prices of certain commodities have become unpredictable over the recent years, and the effect of fundamentals is becoming increasingly negligible in the face of speculators’ decisions on the financial markets. Hence the importance of taking stock of the impact of the mimetic behavior of financial speculators, and of regulating their activity. Originality/value: In contrast to earlier research, introducing the behaviour or psychological impact of recent events on speculative behaviour on the financial markets and, in turn, on the physical markets makes this study unique. Therefore, rather than focusing on the direct impact of financial speculation on oil prices, this study aims to capture the indirect influence. The statistical tool used was ARDL modelling combined with the theory of uncertainty and VNM expected utility theory in order to capture this indirect effect, originally linked to the risk aversion of the various market players. This feature is very important because it allows to predict more precisely future market behavior and trends.
Econometrics = Ekonometria, 2025, Vol. 29, No. 2, s. 1-18
Keywords: financial speculators; herd behavior; WTI crude oil prices; uncertainty theory; ARDL modelling; spekulanci finansowi; zachowania stadne; ceny ropy naftowej WTI; teoria niepewności; modelowanie ARDL